Antarktis-Expedition 1981 mit FFS "Walther Herwig" - Bundesforschungsanstalt für Fischerei (1980)
Johann Heinrich von Thunen-Institute, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung – Information on Fishery research in 2010